The theoretical and methodological transformational process of modem international law development - Chepel, Olha; Karvatska, Svitlana (My University, 2021)
Modern nternational law, created on the basis of the will of states in a mode of reciprocity, is no longer just a horizontally valid right of coordination, but an institutionally arranged law of the world community. In this sense, modern international law has in its positive legally regulated system of coercive measures, in particular the UN Security Council. The UN Charter, acting in an objective manner in relation to all countries of the world, objectively builds a new position of vertical-horizontal influence of law. Due to its creation, modern international law, as it identifies itself in the parameters of the law of the world community, establishes its binding force even in relation to states that have not yet directly agreed to it. In the objective understanding of its essence as the law of the world community, international law is represented in the legal system in accordance with the generally accepted conceptual understanding of law.
Keywords: international law; modern international law; jus gentium